2002
DOI: 10.1046/j.1365-2761.2002.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Epizootiology of Parvicapsulaminibicornis in Fraser River sockeye salmon, Oncorhynchusnerka (Walbaum)

Abstract: Late-spawning Fraser River sockeye salmon, Oncorhynchus nerka, stocks have suffered signi®cant prespawn mortality associated with an unusually early freshwater migration pattern and the myxosporean parasite Parvicapsula minibicornis. Surveys of migrating adult salmon from several spawning populations were conducted in 1999 and 2000 to determine the extent of infection with P. minibicornis, when and where the parasite ®rst becomes detectable during migration, and whether early migrating stocks might be used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 15 publications
(13 reference statements)
6
53
1
Order By: Relevance
“…Epidemiological evidence indicates transmission of P. minibicornis to salmon as they migrate through the lower Fraser River. In adult salmon, prevalence and severity progressively increase with distance migrated in the river (St-Hilaire et al 2002, Jones et al 2003. In the present study and with the exception of the aforementioned 2010 catches, there was a trend of increasing prevalence in juvenile salmon with distance from the Fraser River plume, and this was statistically significant for the Lower Johnstone Strait.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Epidemiological evidence indicates transmission of P. minibicornis to salmon as they migrate through the lower Fraser River. In adult salmon, prevalence and severity progressively increase with distance migrated in the river (St-Hilaire et al 2002, Jones et al 2003. In the present study and with the exception of the aforementioned 2010 catches, there was a trend of increasing prevalence in juvenile salmon with distance from the Fraser River plume, and this was statistically significant for the Lower Johnstone Strait.…”
Section: Discussionsupporting
confidence: 41%
“…Our detection of P. minibicornis confirms an earlier study in which the parasite was reported in juvenile Fraser River sockeye salmon in the Strait of Georgia. St-Hilaire et al (2002) used PCR to demonstrate the infection in approximately 60% of 67 juveniles collected from an unreported location in the lower Strait of Georgia. P. minibicornis was reported in juvenile Chinook salmon O. tshawytscha in the Klamath River, California, USA (Foott et al 2004), where infective actinospores are shed by the polychaete host, Manayunkia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Trophozoites of this parasite (PKX cells) multiplying with internal cleavage are located free among interstitial cells (Clifton-Hadley et al. 1984, Kent et al 1994, St-Hilaire et al 2002, but the possibility that PKX cells are located in small capillaries in the interstitium cannot be excluded. This latter possibility is supported by observations that similar PKX cells occur in other organs as well, and could serve also as an explanation for the route of further development, viz.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, P. minibicornis Kent, Whitaker & Dawe, 1997, which is the best studied species (Kent et al 1997, St-Hilaire et al 2002, seems to follow the Myxidium type development involving initial glomerular stages.…”
Section: Discussionmentioning
confidence: 99%
“…Scholz, personal observation). Therefore, the urban coho mortality phenomenon is dissimilar from other documented circumstances of adult salmon dying prematurely at the spawner life stage because of disease, predation, altered flows, inaccessible spawning habitat, and other nonchemical stressors (St-Hilaire et al 2002;Kocan et al 2004;Keefer et al 2010).…”
Section: Introductionmentioning
confidence: 98%